2001
DOI: 10.1109/20.951188
|View full text |Cite
|
Sign up to set email alerts
|

The role of the spin-orbit coupling strength in the MO effects of magnetic insulators

Abstract: It is currently admitted that the spin-orbit (SO) couplings play a determinant role in the origin of the magneto-optical (MO) properties of magnetic materials. It is unambiguously confirmed that the role of SO coupling of the excited configuration is very weak and that the SO coupling of the ground configuration has a great influence on the MO properties. Furthermore, the symmetry of the magnetic ion environment is a crucial factor. However, contrary to the theoretical results for the Kerr rotation of the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Furthermore, the role of temperature in the MO enhancement is generally ignored in the analyses. Some of our previous articles [7,8] discussed the effect of the SO coupling strength of the ground and excited configurations of rare-earth ions in garnets and trifluorides on the MO effects based on quantum theory. We concluded that the SO coupling strength of the ground configuration had a great and complex effect on FR, but the strength of the excited configuration had surprisingly only a relatively weak influence.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the role of temperature in the MO enhancement is generally ignored in the analyses. Some of our previous articles [7,8] discussed the effect of the SO coupling strength of the ground and excited configurations of rare-earth ions in garnets and trifluorides on the MO effects based on quantum theory. We concluded that the SO coupling strength of the ground configuration had a great and complex effect on FR, but the strength of the excited configuration had surprisingly only a relatively weak influence.…”
Section: Introductionmentioning
confidence: 99%